Strategi Komunikasi Pemasaran Digital dan Tantangan Visual Branding pada UMKM Kuliner: Studi Kasus Camilan Nusantara dan Camilano - Achmad Rio Ardiansah; Salvinia Hawaida; Muhammad Hafizh R; M. Yudha Wiratama; Moch. Magnus R; Moh. Dey Prayogo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study is motivated by the rapid growth of the culinary Micro, Small, and Medium Enterprises (MSMEs) sector in the digital era, which requires business actors to adapt to changes in marketing technology. The purpose of this study is to analyze the implementation of SEO (Search Engine Optimization) based digital marketing strategies and to identify the challenges of visual branding and content production faced by micro business actors. This study employed a descriptive analytical qualitative method with a case study approach involving two culinary MSMEs in East Java, namely Camilan Nusantara and Camilano. Data were collected through in depth interviews with the business owners, observation of operational activities, and documentation of digital assets. The results show that Camilan Nusantara managed to sustain its business through conventional SEO based blog optimization, organically filtering potential products based on market response. Meanwhile, Camilano, which emerged during the pandemic, relied on interpersonal relationships (word of mouth) and Instagram, but faced significant obstacles due to limited skills and visual content production tools. The study concludes that although digital platforms provide broad market access, the consistency of MSME sales is strongly influenced by visual literacy and independent content production capability.